2021
DOI: 10.1093/ecco-jcc/jjab001
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Tissue-Resident Mesenchymal Stem Cells in Chronic Ulcerative Colitis and Crohn’s Disease

Abstract: Background and Aims Little is known about the presence and function of the tissue resident mesenchymal stem cells (MtSCs) within the gastro-intestinal mucosa in health and Inflammatory Bowel Diseases (IBD). The contribution of MtSCs to the generation of inflammatory fibroblasts during IBD is also poorly understood. We hypothesized that IBD-MtSCs are impaired and contribute to the generation of the pathological myofibroblasts in IBD. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…These results indicated that the cells we obtained meet the minimum markers to confirm the MSCs. Previous investigations have found that MSCs or the exosome secreted from MSCs could significantly alleviate ulcerative colitis (Yang et al, 2020;Grim et al, 2021). Consistent with these results, our study showed the conditioned media from MSC significantly attenuated inflammatory responses and improve the colitis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicated that the cells we obtained meet the minimum markers to confirm the MSCs. Previous investigations have found that MSCs or the exosome secreted from MSCs could significantly alleviate ulcerative colitis (Yang et al, 2020;Grim et al, 2021). Consistent with these results, our study showed the conditioned media from MSC significantly attenuated inflammatory responses and improve the colitis.…”
Section: Discussionsupporting
confidence: 92%
“…MSCs are multipotent cells which have been tested in clinical studies for the treatment of IBD. In recent years, MSCs have garnered substantial interest because they have low immunogenicity and are easy to be extracted from adult adipose and bone marrow tissues (Grim et al, 2021). One of the important features of MSCs is the capacity of tri-lineage differentiation, and our result in Figure 1C showed that the cells we obtained had the potentials to differentiate into osteocytes, adipocytes and chondrocytes.…”
Section: Discussionmentioning
confidence: 64%
“…The cells sprinted into the clinic stage center due to their features of versatile development potential, self-renewal, allogenic compatibility, and immunomodulatory effects. MSCs are currently being widely tested as a cellular therapy in chronic intestinal diseases, including IBD, and showed promising clinical outcomes with unmet optimization and improvement [28][29][30], such as in vivo low level of MSC recruitment, and persistence decreased their therapeutic efficacy [31].…”
Section: Discussionmentioning
confidence: 99%
“…Cell therapy for inflammatory bowel diseases seems to be all the more reasonable since these diseases are accompanied by dysfunctions of resident MSCs which are important components of the microenvironment of the intestinal epithelium. Thus, increased proliferative activity of MSCs of the colon mucosa was found in patients with ulcerative colitis, and in patients with Crohn's disease, a loss of the ability of these cells to clonal growth was reported; in both cases, differentiation potentials of MSCs were altered (Grim et al, 2021). There is a fairly large experience of clinical use of MSCs in complex therapy in patients with Crohn's disease and ulcerative colitis.…”
Section: Intestinesmentioning
confidence: 99%